Pharmacognostic Character and Pharmacological Properties of Elaeodendron glaucum (Rottb.) Pers. - Peng-ngummuang, Kanyarat; Thorajak, Piyaporn; Krachai, Puntiwa; Fangkrathok, Niramai; Junlathat, Jintana (Princess of Naradhiwas University Journal, 2022)
Elaeodendron glaucum (Rottb.) Pers. is an indigenous herb belonging to the Celastraceae family. Its bark has been used to treat diabetic wounds according to the folk wisdom of Isan healers and is still being used for continuous healing. The purpose of this research was to study the pharmacognostic character of this plant by studying the macroscopic and microscopic characteristics of the drug, the physicochemical characterization and the chemical identification by high-performance liquid chromatography (HPLC). In addition, the pharmacological effects of its bark were also studied, including antioxidant, anti-inflammatory, and antibacterial activities. The results showed that the bark was reddish-brown, the loss on drying (2.17 ± 0.05 %w/w), total ash (13.97 ± 0.03 %w/w), acid-insoluble ash (0.41 ± 0.11 %w/w), water extractive (13.89 ± 0.20 %w/w) and ethanol extractive values (16.48 ± 0.25 %w/w). Phytochemical studies have shown that the bark extraction of this herb contains flavonoids, tannins and alkaloids. Gallic acid and vanillin were also found as important constituents. Moreover, the aqueous extract of the bark exhibited antioxidant activity (EC50 was 5.50 ± 0.10 and 25.28 ± 0.63 µg/ml when tested by DPPH and ABTS, respectively), anti-inflammatory effect by inhibiting nitric oxide secretion (EC50 was 157.60 ± 1.25 µg/ml), and also revealed antibacterial activity. The results of this study are very useful in the quality control of herbs and are important information to support the use of E. glaucum according to folk wisdom. The finding also helps to expand knowledge in herbal medicine product development.